HRM, institutional complementarities, and performance: the case of the healthcare sector in Jordan - Mohammad, Tamara; Darwish, Tamer K.; Khassawneh, Osama; Wood, Geoffrey (Elsevier, 2025)
Building on the comparative capitalism literature, we aim to understand the impact of HRM practice on hospitals performance within the healthcare sector in Jordan, and the role of HRM in mitigating and overcoming systemic shortfalls. Two different surveys were distributed for both hospital and HR managers across all hospitals. Our findings indicate that certain HR practices are positively associated with performance, despite contextual challenges such as informal networks and cultural limitations that could undermine efficiency. We further tested the potential impact of HR complementarities on performance; nevertheless, the results did not significantly surpass the explanatory power of the individual HR practices. It might have been anticipated that mutually supportive bundles of practices might compensate for systemic weaknesses. However, it may be the case that players have devised solutions in other areas of managerial practice that may be more effective than HRM in compensating for systemic limitations. Our study also highlights that in oligopolistically structured markets, common in private healthcare systems, the effectiveness of HR practices may be less crucial for profitability, though this does not diminish their broader relevance for societal and community outcomes which are beyond the scope of this work.
Keywords: Comparative capitalism; Complementarities; Healthcare; HRM; Organizational performance; Middle East